The Impact of Internal Control on Corporate Performance Through Good Corporate Governance at PT. BPR Tugu Artha Sejahtera, Malang - Muhamad Mukhlis (Sean Institute, 2025)
The impact of Good Corporate Governance (GCG) on performance outcomes, and explores the mediating role of GCG in the linkage between internal control and corporate performance at PT. BPR Tugu Artha Sejahtera in Malang City. The study adopts a quantitative research design using the Partial Least Squares (PLS) analytical method. The population comprises all 100 employees of the company, with the entire population incorporated as the sample through a census approach. The results demonstrate that strong internal control significantly enhances corporate performance. Effective internal control allows the organization to reduce operational risks, improve efficiency, and ensure adherence to regulations, thereby contributing directly to better performance. Moreover, Good Corporate Governance is found to play a pivotal role in elevating corporate performance. Implementing GCG principles, including transparency, accountability, and responsibility, helps create an organized and productive work environment, build trust among stakeholders, and sustain operational stability. In addition, the findings reveal that GCG functions as a mediating factor, strengthening the positive effect of internal control on the company’s performance. Based on these findings, it is recommended that Bank Jatim Malang Branch continues to improve employee competence and service quality, as well as simplify credit procedures to enhance customer satisfaction and loyalty.